Engineering kids health monitoring system in Indonesia - Paputungan, I.V. (Institute of Physics Publishing, 2019)
There is a healthcare program in Indonesia called Pos Pelayanan Terpadu (Posyandu). Services such as nutritional counselling, immunization service, health education and birth preparedness are conducted in the program. All the information collected form such program is still in paper-based document, called Kartu Menuju Sehat (KMS). A development of an electronic KMS (e-KMS) is proposed. This paper presents several related works on e-KMS for Indonesia. This paper derives requirements towards the most workable features for e-KMS based on the literatures. Â© 2019 Institute of Physics Publishing. All rights reserved.